Phenolic acids composition and antioxidant activity of canola extracts in cooked beef, chicken and pork - Brettonnet, Amandine (2010)
Crude polyphenol extracts (15 or 100 mg gallic acid equivalents (GAE)/kg meat) from canola meal reduced the formation of 2-thiobarbituric acid-reactive substances (TBARS) in pre-cooked beef (66–92%), pork (43–75%) and chicken (36–70%). The canola extract contained sinapic (99.7%), ferulic (0.28%) and p-hydroxybenzoic acids (0.07%). The relationship between polyphenol composition and the antioxidant activity of a blend containing of caffeic, cinnamic, p-coumaric, ferulic, gentisic, p-hydroxybenzoic, salicylic, sinapic and syringic acids was described by a first order polynomial model with 2 and 3 way interactions. Sinapic, caffeic and ferulic acids were the highest contributors to the linear term, followed by gentisic, syringic and cinnamic acids. Although the individual activities of salicylic, p-hydroxybenzoic and p-coumaric acids were marginal, all significant synergisms included them.